2007
DOI: 10.1111/j.1365-2818.2007.01832.x
|View full text |Cite
|
Sign up to set email alerts
|

In vivo dynamic light scattering microscopy of tumour blood vessels

Abstract: Summary We present a study investigating the use of dynamic light scattering microscopy based on the temporal laser speckle's contrast that is produced over time by red blood cells (RBCs) flowing inside tumour blood vessels. The proposed noninvasive methodology is capable of producing high‐resolution images of tumour vasculature. The technique is effective at producing images from tissue at a significant depth, as well as potentially having the ability to monitor tumour perfusion. An advantage of this methodol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Laser speckle imaging (LS), also known as laser speckle contrast imaging8, is widely used to visualize the vasculature, blood flow and perfusion in various biomedical applications910, including transcranial imaging of major brain vessels11. LS, which is based on dynamic scattering of diffusively reflected laser light, is sensitive to the movement of red blood cells inside vessels and can therefore be applied for continuous imaging of blood flow dynamics.…”
mentioning
confidence: 99%
“…Laser speckle imaging (LS), also known as laser speckle contrast imaging8, is widely used to visualize the vasculature, blood flow and perfusion in various biomedical applications910, including transcranial imaging of major brain vessels11. LS, which is based on dynamic scattering of diffusively reflected laser light, is sensitive to the movement of red blood cells inside vessels and can therefore be applied for continuous imaging of blood flow dynamics.…”
mentioning
confidence: 99%
“…Although LSCI with a temporal processing scheme for contrast calculation can distinguish microvessels, 13 the vessel contrast can only be improved at the expense of sensitivity to blood flow. Although LSCI has previously been used to image angiogenic events in tumors 3 and wounds, 14 no study has demonstrated or achieved robust flow measurements at a high spatial resolution, as may enable reliable longitudinal assessment of angiogenesis using LSCI. We hypothesized that acquiring and combining LSCI data at multiple exposure times will serve the dual purpose of making blood-flow estimates more robust, as well as improving the CNR over a wide range of physiological blood flows, thus enabling sequential monitoring of the angiogenic microenvironment.…”
Section: Introductionmentioning
confidence: 99%
“…Laser speckle contrast (LSC) imaging (LSCI) is a wide field blood-flow imaging technique that is gaining popularity in neuroscience research, 1, 2 imaging skin tumors, 3 and the retinal vasculature. 4 LSCI has traditionally been used to study shortterm (hours) blood-flow changes in animal models of cerebrovascular reactivity.…”
Section: Introductionmentioning
confidence: 99%
“…The fluorescent light is passing through the set of microscope lens, dichroic mirror and emission band-pass filter 510 − 550 nm, and finally detected by same CCD camera. The analysis of acquired images has been performed by using custom made plug-in 18 for ImageJ (Wayne Rasband, NIH) public domain image processing software.…”
Section: Methodsmentioning
confidence: 99%